The VIMOS Public Extragalactic Redshift Survey (VIPERS): galaxy segregation inside filaments at z ≃ 0.7. Issue 4 (5th November 2016) - Malavasi, N.; Arnouts, S.; Vibert, D.; de la Torre, S.; Moutard, T.; Pichon, C.; Davidzon, I.; Kraljic, K.; Bolzonella, M.; Guzzo, L.; Garilli, B.; Scodeggio, M.; et al.
Abstract: We present the first quantitative detection of large-scale filamentary structure at z ≃ 0.7 in the large cosmological volume probed by the VIMOS Public Extragalactic Redshift Survey (VIPERS). We use simulations to show the capability of VIPERS to recover robust topological features in the galaxy distribution, in particular the filamentary network. We then investigate how galaxies with different stellar masses and stellar activities are distributed around the filaments, and find a significant segregation, with the most massive or quiescent galaxies being closer to the filament axis than less massive or active galaxies. The signal persists even after downweighting the contribution of peak regions. Our results suggest that massive and quiescent galaxies assemble their stellar mass through successive mergers during their migration along filaments towards the nodes of the cosmic web. On the other hand, low-mass star-forming galaxies prefer the outer edge of filaments, a vorticity-rich region dominated by smooth accretion, as predicted by the recent spin alignment theory. This emphasizes the role of large-scale cosmic flows in shaping galaxy properties.